ANALISIS PENGEMBANGAN SEKTOR EKONOMI POTENSIAL KOTA PONTIANAK - Helvira, Reni (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2019)
This research is one of the efforts to find out the potentials of the regions that influence economic growth in Pontianak City from 2013 to 2017 and some of the contributions of these potential sectors to regional economic growth. This study aims to determine which sectors are the base sector and potential sectors to be developed in Pontianak City, and to find out how much influence the base sector and potential sectors have on the development of Pontianak City's GRDP.This study uses secondary data in the form of Gross Regional Domestic Product (GRDP) based on constant prices of Pontianak City and West Kalimantan Province in 2013 to 2017. In this study the analysis method used is Location Quetiont (LQ), Shift Share analysis and Hypothesis Test.The results of the study used the Location Quetiont (LQ) method, sectors that have an LQ index greater than one (LQ> 1) and are the economic base sector, which is the industrial sector, the electricity and gas procurement sector, the water supply sector, waste management, waste and recycling re, the construction sector, the wholesale and retail trade sectors; car and motorcycle repair, transportation and warehousing sector, accommodation and food and beverage supply sector, information and communication sector, financial and insurance services sector, company service sector, government administration sector, compulsory defense and social security sector, education service sector, health service sector and social activities, and other service sectors.The results of the Shift Share analysis method using the differential growth component (DJ) show that there are 6 sectors with a positive average DJ, namely, the water supply sector, waste management, waste and recycling, the wholesale and retail sectors; car and motorcycle repair, accommodation and food and beverage supply sector, company service sector, education sector, health service sector. This indicates that the 6 sectors are growing faster than the same economic sector as the Province of West Kalimantan so that these sectors have high competitiveness and have the potential to be developed to spur economic growth in Pontianak City.Keywords : Economic Potential, Location Quotion and Shift Share